2003
DOI: 10.1101/gad.1134603
|View full text |Cite
|
Sign up to set email alerts
|

RhoB controls Akt trafficking and stage-specific survival of endothelial cells during vascular development

Abstract: Blood vessel formation is a complex morphological process that is only beginning to be understood at the molecular level. In this study, we demonstrate a novel and critical role for the small GTPase, RhoB, in vascular development. RhoB null mice have retarded vascular development in the retina characterized by altered sprout morphology. Moreover, pharmaceutical means to deplete RhoB in neonatal rats is associated with apoptosis in the sprouting endothelial cells of newly forming vessels. Similarly, acute deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
155
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 48 publications
(52 reference statements)
16
155
1
3
Order By: Relevance
“…SGK localized to the nucleus of ER Ăž /-MEFs ( Figure 5b). Staining appeared to be concentrated at the outer margins of the nucleus, reminiscent of a pattern that has been reported for nuclear Akt (Adini et al, 2003). Notably, SGK localized to the cytosol as well as the nucleus in ER -/-MEFs (Figure 5b).…”
Section: Altered Localization Of Gsk-3b and Sgk In Cells Lacking Rhobsupporting
confidence: 69%
See 3 more Smart Citations
“…SGK localized to the nucleus of ER Ăž /-MEFs ( Figure 5b). Staining appeared to be concentrated at the outer margins of the nucleus, reminiscent of a pattern that has been reported for nuclear Akt (Adini et al, 2003). Notably, SGK localized to the cytosol as well as the nucleus in ER -/-MEFs (Figure 5b).…”
Section: Altered Localization Of Gsk-3b and Sgk In Cells Lacking Rhobsupporting
confidence: 69%
“…Loss of rhoB enhances c-Myc protein stability and cell proliferation RhoB can modulate trafficking of Akt (Adini et al, 2003), which through its regulation of GSK-3 has an important role in controlling c-Myc stability (Sears et al, 2000). Previous studies have shown RhoB to limit the proliferation of transformed cells Liu et al, 2001a, b).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…RhoB has a critical role in apoptotic responses to DNA damage, and the GTPase was shown to be a target of farnesyltransferase inhibitors (FTIs) (Lebowitz et al, 1997;Prendergast, 2001a, b;Adini et al, 2003). RhoB, like other Ras family members, is post-translationally modified on a C-terminal motif (CAAX) by farnesylation.…”
Section: Q-myelodysplastic Syndromesmentioning
confidence: 99%